The Capability Approach, Empowerment and Participation
XXV, 428 p. 16 illus., 2 illus. in color.
Keywords: “[The] eventual adoption [of the capability approach] by research and policy analysts depends on the development of methods and applications which demonstrate implementation of the approach in concrete settings. This excellent volume contributes to this important task by linking concepts, methods and application, and by highlighting both the uses and the challenges of the capability approach.” —Ravi Kanbur, Professor, Cornell University, USA “This timely, comprehensive and well-organised volume brings together new work by leading researchers and will be essential reading for all students and researchers interested in the capability approach and its application.” —Mozaffar Qizilbash, Professor, University of York, UK “The capability approach has been centrally influential in moving development policy towards highlighting the importance of processes of empowerment and participation. This book provides useful insights intohow theory translates into the practical application of these valuable concepts.” —Vijayendra Rao, Lead Economist, Development Research Group, World Bank, USA This book explores the linkages between Amartya Sen’s Capability Approach and participatory forms of development – especially those associated with critical pedagogy and empowerment from the bottom-up. It shows how the capability approach and the participatory movement can complement and reinforce each other helping to ensure that democratic principles are respected and become the foundation for sustainable human development. The Capability Approach provides guiding principles for protecting the transformative roots of participation (safeguarding ownership, accountability and empowerment), while participation delivers vital methods for making the Capability Approach operational. Divided into three overlapping parts that focus on concepts, methods and applications, this work draws on diverse fieldwork experiences to unpack power relations, address adaptive preferences, explore individual and collective agency, consider new partnerships for development, and develop innovative concepts. David Alexander Clark is Affiliated Lecturer in the Centre of Development Studies at the University of Cambridge, UK. Mario Biggeri is Associate Professor in the Department of Economics and Management at the University of Florence, Italy. Alexandre Apsan Frediani is Associate Professor in the Bartlett Development Planning Unit at University College London, UK.